Psychological challenges of female caregivers in providing home-based palliative care for patients with advanced cancer: A descriptive-exploratory study - Sharifeh Monemian; Mohammad R. Sharbafchi; Fariba Taleghani (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Family caregivers play a key role in providing care for patients with advanced cancer. Most of this care burden is shouldered by female caregivers in the family. Compared to their male counterparts, female caregivers face numerous psychological challenges in the process of caregiving. The aim of this study was to identify the psychological challenges of female caregivers in providing care to patients with advanced cancer. MATERIALS AND METHODS: This descriptive-exploratory study began with purposive sampling method in 2020-2021 in Isfahan and continued until data saturation was reached. Twenty semi-structured interviews were conducted with female caregivers of patients with advanced cancer and 18 more interviews with providers of health services and supportive-palliative care. The interviews were recorded, transcribed, and analyzed using conventional qualitative content analysis. DISCUSSION: The results were classified into three categories. The first category was psychological reactions that included the four subcategories of depression and anxiety, aggression, mental exhaustion, and death anxiety; the second category was psychological needs which included the three subcategories of need for professional counseling, need for emotional support, and need to prepare for mourning; and the third category was mental occupations which consisted of the two subcategories of feeling of regret and remorse. CONCLUSION: Assessment of psychological challenges is a prerequisite for planning psychological interventions, providing high-quality care, and improving quality of life and satisfaction of caregivers. The findings of this study will contribute to the development of guidelines and empowerment programs for female caregivers providing palliative care.